Outcomes of Modified Tissue Selection Therapy Stapler in the Treatment of Prolapsing Hemorrhoids - Yuan, Chenchen; Zhou, Chongjun; Xue, Rong; Jin, Xiaofeng; Jin, Chun; Zheng, Chenguo (Frontiers in Surgery, 2022)
Tissue selection therapy stapler (TST) is widely used to treat prolapsing hemorrhoids; however, some disadvantages still exist. We describe a modified technique for the treatment of prolapsing hemorrhoids, with the aim to minimize the risk of anal stenosis and anal incontinence and to reduce the impact of postoperative complications of the stapling technique. This modified procedure was successfully applied and preliminary data was observed for the treatment efficacy of modified tissue selection therapy stapler in this study.